Gender Identity Problems in Adolescent Students in the Age of Digital Technologies (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article analyzes the specifics of the formation of immunity against "mass culture" in adolescent students on the basis of a gender approach, thinking that adolescence is a complex, controversial period, the development of self-awareness and self-esteem during this period.